PENGARUH MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI (STUDI PADA PEGAWAI DINAS PERINDUSTRIAN PERDAGANGAN DAN KOPERASI KOTA PALEMBANG) - Susanto, Yohanes (Graduate Program Magister Manajemen Pendidikan, 2017)
This study was purposed at examining the work motivation and leadership style on employee performance. The sample used in this study consisted of 15 respondents from 35 employees. The sampling method used is purposive sampling, the data analysis method used is multiple linear regression analysis. Based on the results of data analysis, the regression equation obtained was Y = 22.100 + 1.167 X1 + 0.420 X2 + e. The result of the research by using t-test that leadership style and work motivation have a significant positive influence on employee performance. The results simultaneously using F-test showed that all independent variables significantly affect employee performance coefficient determinant (R2) is 0,594 which means 59% employee performance is explained by independent variables, where 41% is explained by other variables that are not followed.Â Keywords: Work Motivation, Leadership Style, Employee Performance